'A terrible beauty is born' in Gaza and West Bank - Hasan, Md. Mahmudul (The Daily Star, 2025)
By daring to stay put in the face of death and destruction, for decades Palestinians have been affirming their love for their land and confronting injustice with dignity and resilience. Conversely, the ugliness and hypocrisy stored in the hearts of their oppressors are exposed out there for all to see. While the global conscience is continuously challenged by Israeli aggression, inhumanity and intolerance, as in 1916 Dublin, "a terrible beauty is born" in present-day Gaza and the West Bank.